2008
DOI: 10.1590/s1516-80342008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Análise do desenvolvimento das habilidades diadococinéticas orais em crianças normais e com transtorno fonológico

Abstract: OBJETIVO: Verificar o desempenho de crianças com e sem transtorno fonológico nas provas de diadococinesia e a existência de correlação entre esta e o Índice Porcentagem de Consoantes Corretas Revisado. MÉTODOS: Participaram da pesquisa 35 crianças com idades entre 4:5 e 10:7 anos, sendo 15 diagnosticadas com transtorno fonológico e 20 sem alteração de linguagem. Foram aplicados em todos os sujeitos: prova diadococinética, anamnese, provas de fonologia e vocabulário do teste de linguagem Infantil ABFW, avaliaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 17 publications
(27 reference statements)
1
24
0
10
Order By: Relevance
“…The complementary task of oral DDK used at the present research may provide evidences of a deficit at the speech motor programming (10,20) . Both the application and analysis of the oral DDK testing depend on: the age of the participants, the data collection (the command given to the subject), the duration of the sequences, the type of sequence analyzed and the acoustic treatment of the recorded data.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The complementary task of oral DDK used at the present research may provide evidences of a deficit at the speech motor programming (10,20) . Both the application and analysis of the oral DDK testing depend on: the age of the participants, the data collection (the command given to the subject), the duration of the sequences, the type of sequence analyzed and the acoustic treatment of the recorded data.…”
Section: Discussionmentioning
confidence: 75%
“…Both the application and analysis of the oral DDK testing depend on: the age of the participants, the data collection (the command given to the subject), the duration of the sequences, the type of sequence analyzed and the acoustic treatment of the recorded data. These questions are addressed by many published studies (5,9,10,12,14,15,21,22) what turns difficult the comparison between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phonological disorders can appear at different levels of language processing or involving phonological information such as discrimination of sounds, recognition of phonological contrast (different sounds for each phoneme), and the representation of these contrasts in the lexicon. The modified sounds of speech production due to inappropriate use of phonological rules or not the accuracy articulation can be classified as phonological disorder 8 . These disorders may be related to difficulties with the organization of phonological rules of the language that characterizes a cognitive-linguistic difficulty with auditory perception and / or production of sounds.…”
Section: Methodsmentioning
confidence: 99%
“…Studies found tongue praxis difficulties, difficulties in moving articulators during praxis tests and in the quick repetition of syllables, as well as a lower speech speed in atypical children compared to the ones with no deficit in the sound system (13)(14)(15)(16) .…”
Section: Threementioning
confidence: 99%